2015
DOI: 10.1136/bmjopen-2015-008156
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome and computer exposure at work in two large complementary cohorts

Abstract: ObjectivesThe boom in computer use and concurrent high rates in musculoskeletal complaints and carpal tunnel syndrome (CTS) among users have led to a controversy about a possible link. Most studies have used cross-sectional designs and shown no association. The present study used longitudinal data from two large complementary cohorts to evaluate a possible relationship between CTS and the performance of computer work.Settings and participantsThe Cosali cohort is a representative sample of a French working popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
1
33
0
1
Order By: Relevance
“…Studies focused on office workers report mixed results on associations between computer use and musculoskeletal symptoms . Our results indicated that computer use was significantly protective for hand and neck pain, which is consistent with a previous study on two large general population cohorts (France and the United States of America) that observed no association between computer work and new cases of carpal tunnel syndrome . In general population studies, office workers are compared to workers in other job sectors, who are more highly exposed to other physical factors such as repetition, forceful exertions, vibration, and awkward postures.…”
Section: Discussionsupporting
confidence: 87%
“…Studies focused on office workers report mixed results on associations between computer use and musculoskeletal symptoms . Our results indicated that computer use was significantly protective for hand and neck pain, which is consistent with a previous study on two large general population cohorts (France and the United States of America) that observed no association between computer work and new cases of carpal tunnel syndrome . In general population studies, office workers are compared to workers in other job sectors, who are more highly exposed to other physical factors such as repetition, forceful exertions, vibration, and awkward postures.…”
Section: Discussionsupporting
confidence: 87%
“…In included studies, both duration and input frequency of keyboard and mouse were assessed, whereas for computer and VDT, only the duration of use was assessed. We found nine studies in which the exposure was assessed using self-reports,26–31 33 35 40 while in two studies (the NUDATA and the PROMO study, respectively) both self-reports and software recordings (ie, using dedicated software to record the duration and input frequency of use) of screen work were reported6 7 32 36–39; in one study, the exposure was assessed using a job–exposure matrix 27. No studies on laptop, notebook and/or tablet computer use were identified, despite our aim and search to include such studies in this particular review.…”
Section: Resultsmentioning
confidence: 99%
“…However, JEMs can be useful to the study of a wide range of health outcomes. There has been recent interest in applying JEMs to study the effects of workplace physical demands on musculoskeletal disorders, pregnancy outcomes, hernias, and cardiovascular disease . Such job‐related data can be obtained through The Occupational Information Network (O*NET) provided by the U.S. Department of Labor.…”
Section: Introductionmentioning
confidence: 99%